Kenelle yritystuet menevät? - Mika Pajarinen; Petri Rouvinen; Pekka Ylä-Anttila (The Research Institute of the Finnish Economy (ETLA), 2009)
Statistics Finland maintains a database which includes firm level data on public support in Finland. During this study it contained data from the years 2000-6. So far the data has been underutilized in economic and statistical analyses. We use the database in this descriptive study mainly to test the usability of the database. We analyze, for example, the scale, ways of use, and allocation of public support. We count as public support all the instruments in the database from loans and guarantees to direct employment and r&d subsidies. The results indicate that public support to firms is quite common, larger firms have higher probability of receiving public support than smaller ones, and that receiving public support once increases the probability to apply for and to receive it in the following years. The database seems to offer a quite good starting point for firm level public support studies, although it still lacks some essential public support instruments.
Keywords: H81; L53; O25; Y10; 330; Public support; public finance; industrial policy; Finland; Industriepolitik; Subvention; Finnland